2011
DOI: 10.1111/j.1472-8206.2011.00978.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of controlled ingestion of kaolinite (5%) on food intake, gut morphology and in vitro motility in rats

Abstract: Geophagia is found in various animal species and in humans. We have previously shown that spontaneously ingested kaolinite interacts with the intestinal mucosa modifies nutrient absorption and slows down gastric emptying and intestinal transit in rats in vivo. However, the precise mechanisms involved are not elucidated. The aim of this work was to investigate the effects of controlled kaolinite ingestion on food intake, gut morphology and in vitro motility in rats. Male Wistar rats were fed with 5% kaolinite i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 44 publications
1
7
0
1
Order By: Relevance
“…Our data indicate that kaolinite may modulate activities of enteric nerves at 14 days of imposed ingestion. These data emphasized our previous results which indicated that spontaneous mechanical activities were depressed in both jejunum and proximal colon and that the tone increase was enhanced in the presence of acetylcholine in jejunum at 14 days of kaolinite ingestion in rats [19]. Furthermore, we showed that the decrease of the relaxation induced by L-NNA was significantly reduced in the jejunum, whereas the contraction was enhanced in the proximal colon at 14 days of kaolinite ingestion.…”
Section: Effects Of Kaolinite Ingestion On Leptin Effects In the Pressupporting
confidence: 89%
See 4 more Smart Citations
“…Our data indicate that kaolinite may modulate activities of enteric nerves at 14 days of imposed ingestion. These data emphasized our previous results which indicated that spontaneous mechanical activities were depressed in both jejunum and proximal colon and that the tone increase was enhanced in the presence of acetylcholine in jejunum at 14 days of kaolinite ingestion in rats [19]. Furthermore, we showed that the decrease of the relaxation induced by L-NNA was significantly reduced in the jejunum, whereas the contraction was enhanced in the proximal colon at 14 days of kaolinite ingestion.…”
Section: Effects Of Kaolinite Ingestion On Leptin Effects In the Pressupporting
confidence: 89%
“…As we have previously shown that kaolinite induces an increase in food intake and in plasmatic levels of leptin at 14 days of ingestion , leptin may be involved in the changes in mechanical activities and enteric nerves activities. Indeed, leptin has been shown to activate guinea pig colonic submucosal and myenteric plexus and to modulate enteric neurotransmission in rat colon and particularly nitrergic neurotransmission (unpublished data).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations